Citizen hobo : how a century of homelessness shaped America - DePastino, Todd (University of Chicago Press, 2003)
In the years following the Civil War, a veritable army of homeless men swept across America's "wageworkers' frontier" and forged a beguiling and bedeviling counterculture known as "hobohemia." Jealously guarding the American road as the preserve of white manhood, hoboes swaggered onto center stage of the new urban culture. DePastino tells the epic story of hobohemia's rise and fall, drawing on sources ranging from diaries, letters, and police reports to movies and memoirs. He also, crucially, shows how the hobo army prompted the creation of an entirely new social order and political economy, influencing the creation of welfare state measures, the promotion of mass consumption, and the suburbanization of America. This sweeping retelling of American nationhood in light of enduring struggles over "home" does more than chart the change from "homelessness" to "houselessness," it offers a new context for thinking about Americans' struggles against inequality and alienation.--From publisher description.